Desiccation Induced Conjunctival Monocyte Recruitment and Activation - Implications for Keratoconjunctivitis - Alam, Jehan; de Paiva, Cintia S.; Pflugfelder, Stephen C. (Frontiers in Immunology, 2021)
Background: Lacrimal gland secretory dysfunction in Sjögren syndrome (SS) causes ocular surface desiccation that is associated with increased cytokine expression and number of antigen-presenting cells (APCs) in the conjunctiva. This study evaluated the hypothesis that desiccating stress (DS) alters the percentage and gene expression of myeloid cell populations in the conjunctiva. Methods: DS was induced by pharmacologic suppression of tear secretion and exposure to drafty low humidity environment. Bone marrow chimeras and adoptive transfer of CD45.1+ bone marrow cells to CD45.2+ C-C chemokine receptor 2 knockout (CCR2-/-) mice were used to track DS-induced myeloid cell recruitment to the conjunctiva. Flow cytometry evaluated myeloid cell populations in conjunctivae obtained from non-stressed eyes and those exposed to DS for 5 days. CD11b+ myeloid lineage cells were gated on monocyte (Ly6C), macrophage (CD64, MHCII) and DC (CD11c) lineage markers. NanoString immune arrays were performed on sorted MHCII+ and MHCII- monocyte/macrophage cell populations. Results: DS significantly increased the recruitment of adoptively transferred MHCII positive and negative myeloid cells to the conjunctiva in a CCR2 dependent fashion. The percentage of resident conjunctival monocytes (Ly6C+CD64-) significantly decreased while CD64+MHCII+ macrophages increased over 5 days of DS (P<0.05 for both). Comparison of gene expression between the MHCII- monocyte and MHCII+ populations in non-stressed conjunctiva revealed a  2 log2 fold increase in 95 genes and decrease in 46 genes. Upregulated genes are associated with antigen presentation, cytokine/chemokine, M1 macrophage and NLRP3 inflammasome pathways. DS increased innate inflammatory genes in monocytes and MHCII+ cells and increased M1 macrophage (Trem1, Ido1, Il12b, Stat5b) and decreased homeostasis (Mertk) and M2 macrophage (Arg1) genes in MHCII+ cells. Conclusions: There are myeloid cell populations in the conjunctiva with distinct phenotype and gene expression patterns. DS recruits myeloid cells from the blood and significantly changes their phenotype in the conjunctiva. DS also alters expression of an array of innate inflammatory genes. Immature monocytes in the unstressed conjunctiva appear to cascade to MHCII+ macrophages during DS, suggesting that DS promotes maturation of monocytes to antigen presenting cells with increased expression of inflammatory genes that may contribute to the pathogenesis of SS keratoconjunctivitis sicca.